2001
DOI: 10.1095/biolreprod65.3.718
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of Neutrophils in Germ Cell-Specific Apoptosis Following Ischemia/Reperfusion Injury of the Mouse Testis1

Abstract: This study investigates the role of neutrophils in ischemia-induced aspermatogenesis in the mouse. Previous studies in the rat have demonstrated that ischemia-inducing testicular torsion followed by torsion repair and reperfusion resulted in germ cell-specific apoptosis. This was correlated with an increase in neutrophil adhesion to subtunical venules, an increase in reactive oxygen species, and increased expression of several apoptosis-associated molecules. In the present investigation, wild-type C57BL/6 mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
179
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(187 citation statements)
references
References 39 publications
7
179
1
Order By: Relevance
“…In the present study, torsion and detorsion-induced I/R injury was found to cause morphological changes and increase the polymorphonuclear cells in the seminiferous tubules, consisting with the literature findings (18). We also observed germinal epithelial cell loss and degenerative changes in spermatogonia and spermatids.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, torsion and detorsion-induced I/R injury was found to cause morphological changes and increase the polymorphonuclear cells in the seminiferous tubules, consisting with the literature findings (18). We also observed germinal epithelial cell loss and degenerative changes in spermatogonia and spermatids.…”
Section: Discussionsupporting
confidence: 90%
“…E-selectin acts by tethering neutrophils and facilitating their slow rolling along endothelial cells (53,54). Neutrophil recruitment to affected organs is one of the hallmarks of I/R injury and E-selectin serves a critical role in neutrophil recruitment to the testes following I/R and the resulting germ cell-specific apoptosis (55). Blocking E-selectin with function-blocking monoclonal E-selectin antibody, even after the onset of reperfusion inhibits neutrophil recruitment to the I/R-induced murine testes.…”
Section: Interaction With Neutrophilsmentioning
confidence: 99%
“…Unilateral testicular torsion was created by scrotal approach through a midline incision, the left testis twisted 720°in a counter clockwise direction and by fixing the testis to the scrotum with a 6-0 nylon suture passing through the tunica albuginea and dartos [27]. Animals underwent 2 h of unilateral testicular ischemia.…”
Section: Spermatic Cord Torsionmentioning
confidence: 99%